Perancangan Sistem Pengendalian Persediaan dengan Economic Order Quantity dan Reorder Point pada UMKM BPK Legend Batam - Hery Haryanto; Novita Nelvi (Lembaga Pengembangan Kinerja Dosen, 2026)
UMKM BPK Legend Batam is a Batak culinary business that serves Karo Roast Pork (BPK) as its main dish along with side dishes such as soup, saksang, and fried Indomie B2. In its operational activities, food product inventory management is still done manually and based on estimates, which can potentially lead to excess or shortages of ready-to-sell products. This situation can result in a decline in product quality, wasteful spending, and lost sales opportunities when demand increases. The objective of this community service activity is to design a more effective and efficient food product inventory control system through the application of the EOQ and ROP methods. The methods used include observation, interviews, and analysis of sales data and product availability per period. The results of the activity show that the application of EOQ is able to determine the optimal product inventory quantity, while ROP provides guidelines for the right time to replenish products. The product inventory control system that was designed helps BPK Legend MSMEs in reducing inventory costs, maintaining product availability, and supporting smooth service to customers.